Effect of Four Grape Varieties on the Physicochemical and Sensory Properties of Unripe Grape Verjuice - Najiba Salah Eddine; Sami Tlais; Ali Alkhatib; Rasha Hamdan (International Journal of Food Science)
Verjuice is a sour-tasting juice obtained from the mechanical pressing of unripe grapes. The significance of verjuice as food product includes but not limited to its richness in antioxidant compounds, its usage as an alternative to lemon and vinegar, and also its production which can reduce the losses of lower quality grapes and waste from grape thinning. In this study, a survey for the common Lebanese traditional preparation methods for verjuice was done and physicochemical properties of four Lebanese verjuice varieties Tfayfihi, Baytamoni, Black, and Obeideh along with their sensory evaluation by consumers were studied. Results showed that “Black” grape verjuice has the highest density (1.01±0.003 g/L), titratable acidity (4.51 g/L±0.03), total soluble solids (5.38°Brix±0.3), and polyphenol content (676.1 mg/L±6.8); verjuice processed from the Baytamoni grape variety has the highest browning index (0.432±0.002) and color intensity (1.18±0.007); “Obeideh” grape verjuice has the highest pH (2.55±0.006); and “Tfayfihi” grape verjuice has the highest radical scavenging potential (91.76%±0.43) and moisture content (95.85%±0.19). Both “Tfayfihi” and “Black” grape verjuice has the highest total suspended solids (40 g/L±1.3 and 40 g/L±2.9, respectively) among all studied verjuice. There is no difference in taste between the four verjuice varieties which we studied, but there is a color preference for the “Tfayfihi” verjuice. The use of different varieties of grapes in the processing of verjuice affects the physicochemical and sensory properties and results in selection of grape varieties being favorable in the processing of verjuice with respect to factors such as polyphenol content and color of the final product.